Effects of Constant and Sinusoidal Display Lag on Sickness During Active Exposures to Virtual Reality - Palmisano, Stephen; Morrison, Vanessa; Allison, Robert S.; Davies, Rodney G.; Kim, Juno (2024 IEEE Conference on Virtual Reality and 3D User Interfaces Abstracts and Workshops (VRW), 2024)
When we move our heads in virtual reality (VR), display lag creates differences between our virtual and physical head pose (DVP). This study examined whether objective estimates of these DVP could be used to predict the sickness caused by different types of lag. We found that adding constant and time-varying lag to simulations generated similar levels of sickness - with all added lag conditions producing more severe sickness than our baseline control. Consistent with the DVP hypothesis, the spatial magnitude and temporal dynamics of the DVP were both found to predict cybersickness severity during active HMD VR.